How do predators generalize warning signals in simple and complex prey communities? Insights from a videogame. Issue 1921 (26th February 2020) - Arias, Mónica; Davey, John W.; Martin, Simon; Jiggins, Chris; Nadeau, Nicola; Joron, Mathieu; Llaurens, Violaine
Abstract : The persistence of distinct warning signals within and between sympatric mimetic communities is a puzzling evolutionary question because selection favours convergence of colour patterns among toxic species. Such convergence is partly shaped by predators' reaction to similar but not identical stimulus (i.e. generalization behaviour), and generalization by predators is likely to be shaped by the diversity of local prey. However, studying generalization behaviour is generally limited to simple variations of prey colour patterns. Here, we used a computer game played by humans as surrogate predators to investigate generalization behaviours in simple (4 morphs) and complex (10 morphs) communities of unprofitable (associated with a penalty) and profitable butterflies. Colour patterns used in the game are observed in the natural populations of unprofitable butterfly species such as Heliconius numata . Analyses of 449 game participants' behaviours show that players avoided unprofitable prey more readily in simple than in complex communities. However, generalization was observed only in players that faced complex communities, enhancing the protection of profitable prey that looked similar to at least one unprofitable morph. Additionally, similarity among unprofitable prey also reduced attack rates only in complex communities. These results are consistent with previous studies using avian predators but artificial colour patterns and suggest that mimicry is more likely to evolve in complex communities where increases in similarity are more likely to be advantageous.